Analisis Pengalaman Pengguna (User Experience) Aplikasi PRUforce menggunakan Metode Usability Testing dan User Experience Questionnaire (UEQ) (Studi Kasus pada PT Prudential Life Assurance) - Malik Fajar; Fatwa Ramdani; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT PRUDENTIAL LIFE ASSURANCE launches a PRUforce application for marketers. In providing services, marketers use application-based information technology. Prudential staff encountered interface problems when using PRUforce. The usability testing method and user experience questionnaire (UEQ) are the methods used in research by researchers. The steps in compiling the research started from literature studies, data collection and processing sessions, discussed analysis results sessions and conclusions and suggestions. There were 5 PRUforce users who were then performed usability testing. The test provides a value in terms of the effectiveness aspect with a value of 100% which indicates that the user can complete the task, in terms of efficiency it is obtained a value of 0.01 goals / second which means the level of speed of the user in completing the task and in terms of satisfaction in the value range of 60% -65% which indicates the level PRUforce application user satisfaction. Furthermore, the UEQ questionnaire was distributed to 30 respondents to test the user experience and a score with an average of 2.37 which was produced in terms of perspicuity, attractiveness, dependability, stimulation, efficiency and novelty aspects, which showed that the PRUforce application tended to evaluate the assessment towards good / positive direction according to user experience.